Meningkatkan Daya Saing Mahasiswa melalui Pelatihan Kepemimpinan Inklusif dan Literasi Digital Menuju Masyarakat 5.0 Pada Mahasiswa Universitas Palangka Raya - Rahman, Rahman; Tonich, Tonich; Hariatama H, Fendy; Putri, Windy Utami; Oktaria, Merisa (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
The era of the Industrial Revolution 4.0 has brought significant changes to higher education, compelling students to adapt to rapid digital transformation. However, more complex challenges have emerged with the introduction of the Society 5.0 concept—a future society based on advanced technology that places humans at the center of innovation (human-centered society). As part of the young generation in Central Kalimantan, students at the University of Palangka Raya need to be equipped with multidimensional skills. The need for digital literacy has become increasingly urgent in the Society 5.0 era, where humans and technology are integrated in solving real-life problems. The method used in this community service activity was a training program focusing on inclusive leadership and digital literacy. The training, conducted face-to-face, was carried out smoothly and successfully. Overall, the training program aimed at enhancing students' understanding of these concepts can be considered effective. This success was evident as participants were able to perform leadership simulations and deliver presentations during discussion sessions that aligned with the examples and materials provided by the trainers. The main benefits gained by the students were new insights into inclusive leadership in a digital context and valuable hands-on experience.